The impact of imagery training on achievement motivation among young swimmers aged 10-15 years - Yahya Eko Nopiyanto; Dian Pujianto; Defliyanto Defliyanto; Bayu Insanistyo; Cahyo Wibowo; Dewi Sartika; Silvi Aryanti; Fitri Agung Nanda (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Achievement motivation is a critical factor in the performance and development of young athletes. It drives them to set and pursue goals, overcome obstacles, and succeed in sports. Understanding and enhancing achievement motivation can significantly impact young athletes' progress and performance. This study aims to examine the effect of imagery training on the achievement motivation of young swimmers to achieve, especially in commitment, goal setting, self-confidence, and engagement. The research design uses one group pre-test and post-test. A sample of 20 young swimmers participated in the study. Achievement motivation was assessed using standardized pre-test and post-test measures. The independent sample t-test revealed a highly significant difference between pre-test and post-test means (t = -26.937, p = 0.000), confirming the effectiveness of imagery training. These improvements suggest that imagery training can improve swimmers' commitment, goal-setting ability, self-confidence, and engagement in training. Although this study has several limitations, such as limited sample size and short training duration, the results confirm the importance of imagery training as an effective method in supporting mental development and performance improvement in young swimmers. Further research is recommended to address these limitations and explore the long-term effects of imagery training.